Mexico : Financial Sector Assessment Program Update; Technical Note; Strategic Issues in Development Bank Reform. (IMF Staff Country Reports; Country Report ;, 2007)
This technical note on strategic issues in Development Bank (DB) reform for Mexico examines advances in the area of DB and funds in 2000-05. There have been significant but uneven changes in the institutional setting, instruments, transparency of subsidies, and performance behavior of DBs during 2000-05. Risk-adjusted capital ratios have diminished since 2000, in part owing to more stringent regulatory requirements, but are comparable with those of commercial banks, as the same regulatory and supervisory standards are applied.